Crystalline grain refinement toughened isotactic polypropylene through rapid quenching of stretched melt. (22nd February 2021) - Chen, Xin; Zhang, Zhen; Chen, Bin; Liu, Chuntai; Zhang, Shixun; Cao, Wei; Wang, Zhen
Abstract: Nanoscale grain refinement is a mature and powerful tool to enhance the mechanical and physical properties of metals and alloys. However, similar cases are rarely reported in the widely used semicrystalline polymers. Herein, we demonstrate a feasible strategy to fabricate the ultrafine-grained isotactic polypropylene (iPP) by rapid quenching of stretched melt. The grain refinement happens to regularly arranged nano-lamellae in both thickness and lateral directions, leading to an order of magnitude improvement in the number density of lamellae compared to normal melt crystallization. We have shown that such grain refinement greatly enhances the tensile toughness of iPP material without sacrificing the modulus and strength. Rope-like fracture morphology is observed in the toughened samples after the mechanical tests. It is indicated that the refined crystalline grains with low structural stability probably favor the formation of fibrils. This work provides a generalized approach to mechanically toughen the semicrystalline polymers by grain refinement on the nano-lamellar scale. Graphical abstract: Image 1 Highlights: - Rapid quenching of stretched melt leads to a refinement of lamellar crystal in both thickness and lateral directions. - Ultrafine-grained iPP corresponds to an order of magnitude improvement in the number density of lamellae. - Grain refinement on the nano-lamellar scale greatly enhances the tensile toughness of material.